2016
DOI: 10.5194/acp-16-12081-2016
|View full text |Cite
|
Sign up to set email alerts
|

Sea salt emission, transport and influence on size-segregated nitrate simulation: a case study in northwestern Europe by WRF-Chem

Abstract: Sea salt aerosol (SSA) is one of the major components of primary aerosols and has significant impact on the formation of secondary inorganic particles mass on a global scale. In this study, the fully online coupled WRF-Chem model was utilized to evaluate the SSA emission scheme and its influence on the nitrate simulation in a case study in Europe during 10-20 September 2013. Meteorological conditions near the surface, wind pattern and thermal stratification structure were well reproduced by the model. Nonethel… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
37
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
1
1

Relationship

3
4

Authors

Journals

citations
Cited by 40 publications
(43 citation statements)
references
References 79 publications
6
37
0
Order By: Relevance
“…This is comparable with other models (Im et al, 2015). However, short periods with strong overestimations of [NO − 3 ] were also observed in previous New scheme (this study) 50 % * * Suggested by Sintermann et al (2012), Backes et al (2016), and Chen et al (2016b). studies. This seems to be the case for the HOPE Melpitz campaign simulation, during which COSMO-MUSCAT highly overpredicted [NO − 3 ] over Germany in this study (Fig.…”
Section: Improvement Of the Particulate Nitrate Predictionsupporting
confidence: 74%
See 3 more Smart Citations
“…This is comparable with other models (Im et al, 2015). However, short periods with strong overestimations of [NO − 3 ] were also observed in previous New scheme (this study) 50 % * * Suggested by Sintermann et al (2012), Backes et al (2016), and Chen et al (2016b). studies. This seems to be the case for the HOPE Melpitz campaign simulation, during which COSMO-MUSCAT highly overpredicted [NO − 3 ] over Germany in this study (Fig.…”
Section: Improvement Of the Particulate Nitrate Predictionsupporting
confidence: 74%
“…The emission of NH 3 was reduced by 50 %, since over 90 % of NH 3 emissions in Europe are contributed by agricultural sources (Hertel et al, 2011;Erisman et al, 2008;Reidy et al, 2008), and agriculture emissions of NH 3 are overestimated by ∼ 50 % or even more (Sintermann et al, 2012;Backes et al, 2016). Also, Chen et al (2016b) adopted the same NH 3 emission inventory in the WRF-Chem model and reported that total NH 3 was overestimated by a factory of ∼ 2 at Melpitz during the campaign period. The modelled dust emissions depend on surface wind friction velocities, sur- face roughness, soil particle size distribution, and soil moisture (Heinold et al, 2011).…”
Section: The Model System Cosmo-muscatmentioning
confidence: 99%
See 2 more Smart Citations
“…However, not only the mass concentration but also the particle mass size distribution (PMSD) are 50 essential for evaluating the direct radiative forcing of nitrate (DRFnitrate) (IPCC, 2013;Murphy et al, 1998;Kok et al, 2017). Besides leading to the increase of total nitrate mass, interactions with sea-salt aerosol also have a 're-distribution effect' on nitrate PMSD which shifts nitrate from sub-to super-micron sizes (e.g., Chen et al, 2016a, see also Fig. 1).…”
Section: Introductionmentioning
confidence: 99%